Characterization of leadership styles by analyzing social networks (Journal of Business, Universidad del Pacífico (Lima, Peru), 2014)
The study presents an analysis of networks to characterize the leadership styles in an institution volunteer, complementary or alternative to classic questionnaires to measure leadership. The study raises test questions to identify friendly relations and prominent leaders in the leadership dimensions of transformational, transactional and passive / avoidant and analyzes, for each of them, the metrics of the network structure as a whole and the role each individual actor. The study exploratory level, based on the opinion of 9 members of a specific project, allowed to show the benefits of network analysis applied to the subject of leadership: (i) identified that the climate of "respect and trust", "enthusiasm" and "concern for the welfare of the people" dominate the organization; and (ii) the individual role of each leader was identified. Three leaders who are considered as the best friends and care about the welfare of others were identified, but one of them stands for broadcasting "greater respect and trust" and is "an example to follow"; while the other two leaders stand out as being more "enthusiastic and optimistic" and "promote innovation and creativity," among other findings.
Keywords: Leadership; Network analysis; Huma Resource Management